2009
DOI: 10.3991/ijim.v4i1.1057
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Introduction of Mobile Banking in Jordan Using Technology Acceptance Model

Abstract: Abstract-The continuously growing number of mobile users demonstrates that more and more users seek to benefit from the freedom afforded without the need for cables, time and place. The mobility is the driving force behind the new global economy, with mobile banking, banks offer a new revolutionize services and giving their consumers more options than ever before. I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…There is still a lot of room for advancement in mobile banking operations and services such account transfers, balance enquiries, bill payments, stop-payment requests, and some even offer online loan and credit card applications. Therefore, it is important to comprehend user acceptance of mobile banking and pinpoint the variables driving users' inclinations to use mobile banking [1]. Mobile payment is becoming more commonplace as mobile the organisation expands quickly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is still a lot of room for advancement in mobile banking operations and services such account transfers, balance enquiries, bill payments, stop-payment requests, and some even offer online loan and credit card applications. Therefore, it is important to comprehend user acceptance of mobile banking and pinpoint the variables driving users' inclinations to use mobile banking [1]. Mobile payment is becoming more commonplace as mobile the organisation expands quickly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relevant studies confirmed that TAM was used as the core framework for analysis the acceptance of the mobile system. Many studies investigated users attitude on mobile technology through adoption of tools or consumer application such as mobile banking [44], google translation [45], e-learning in university system [46,47] and mobile commerce adoption via mobile applications [48]. TAM model also used for organization assessment for the evaluate e-commerce assessment for SMEs [49] and university assessment [50] in Thailand.…”
Section: Tammentioning
confidence: 99%
“…For instance, the mobile banking services such as M-Pesa (available in Africa), IMPS (Inter-Bank Mobile Payment Service) in India, bKash (available in Bangladesh), and STCpay (available in Saudi Arabia) have completely changed the way banks operate [6][7][8]. Mobile banking is also a dominant form of banking in Jordan [9,10]. MTV technology is used in mobile Fintech services in Bangladesh [11].…”
Section: Introductionmentioning
confidence: 99%